2018
DOI: 10.1177/1591019918776207
|View full text |Cite
|
Sign up to set email alerts
|

Procedural and clinical outcomes of endovascular recanalization therapy in patients with cancer-related stroke

Abstract: Objective Embolism due to coagulopathy might be the main pathomechanism underlying cancer-related stroke (CRS). CRS patients with a large artery occlusion could be candidates for endovascular recanalization therapy (ERT), although its procedural and clinical outcomes are not well known. This study aimed to investigate the procedural and clinical outcomes of ERT in CRS patients and the characteristics associated with outcomes compared with those of conventional stroke … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 21 publications
7
63
0
2
Order By: Relevance
“…All patients who had undergone chemotherapy had received at least one thrombogenic agent, which may have increased the risk of stroke [4]. Functional outcome measures showed a significant improvement after thrombectomy, in line with previous reports [13,14]. Patient characteristics including site of thrombus and cardiovascular risk profile (Tables 1 and S1) were comparable to those from a recent prospective trial in patients not stratified for cancer [15].…”
Section: Discussionsupporting
confidence: 82%
“…All patients who had undergone chemotherapy had received at least one thrombogenic agent, which may have increased the risk of stroke [4]. Functional outcome measures showed a significant improvement after thrombectomy, in line with previous reports [13,14]. Patient characteristics including site of thrombus and cardiovascular risk profile (Tables 1 and S1) were comparable to those from a recent prospective trial in patients not stratified for cancer [15].…”
Section: Discussionsupporting
confidence: 82%
“…This is probably because ischemic stroke frequently occurs at the late stage of malignancy when the condition of the patients is not as good as that of the participants in clinical trials ( 3 ). Short-term prognosis for patients who underwent EVT with concomitant malignancy has been reported by others, and the results were mostly similar ( Table 3 ) ( 21 , 22 ). Jung et al showed the result of EVT for 19 patients with active cancer and reported that only three patients (16%) were able to attain functional independence, while the rest were either bedridden (4 patients; 21%) or died (12 patients; 63%) ( 21 ).…”
Section: Discussionsupporting
confidence: 81%
“…Short-term prognosis for patients who underwent EVT with concomitant malignancy has been reported by others, and the results were mostly similar ( Table 3 ) ( 21 , 22 ). Jung et al showed the result of EVT for 19 patients with active cancer and reported that only three patients (16%) were able to attain functional independence, while the rest were either bedridden (4 patients; 21%) or died (12 patients; 63%) ( 21 ). Sallustio et al showed that functional independence was achieved in 42% of the patients, while they noticed a mortality rate of 29% ( 22 ).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, the response to recanalization therapies may differ between stroke patients with and without cancer. 55,76 A recent report of thrombectomy specimens in patients with stroke and active cancer (n=16) showed that retrieved thrombi were mostly platelet-risk, suggesting the role of antiplatelet in prevention of Vol. 22 / No.…”
Section: Prevention Of Stroke In Cancer Coagulopathymentioning
confidence: 99%